Relative efficiency of sawmill types operating in Uganda's softwood plantations - Kambugu, Robert K.; Banana, Abwoli Y.; Zziwa, Ahamada; Agea, Jacob G.; Kaboggoza, John R. S. (Uganda Journal of Agricultural Sciences, 2005)
The overall aim of this study was to determine the appropriate saw milling technologies that should be promoted for use in Uganda's softwood plantation. Conversion efficiency, sawing accuracy, and sawing capability of four sawmill categories were evaluated. Data were collected from sawing of 604 good Aquality logs using eleven Rolling ATable Sawmills, Dimensional Swivel Sawmills, Band Sawmills, and Locally Afabricated Snwmills. Sawing accuracy data were collected from 165 boards in three timber sizes (75 mm x 50 mm, 100 mm x 50 mm, 150 mm x SO mm). Sawing capability was assessed from saw blade parameters, merchantable timber size, and size of available logs. AN OVA was used to show differences in recovery and sawing accuracy between and within sawmills. Band sawmills exhibited the most efficient sawmill technology for converting logs into sawn timber while rolling-table sawmills were more efficient than dimensional swivel and locally manufactured sawmills. Band sawmills were more accurate than sawmills in the other categories. Therefore, band sawmills should be promoted in Uganda and mechanical modifications carried out on the swivel and locally-manufactured sawmills operating in softwood plantations to improve their feed A work and setwork mechanisms
Keywords: sawmill; conversion; efficiency; softwood